Diffusion dynamics of synaptic molecules during inhibitory postsynaptic plasticity - Petrini, Enrica Maria; Barberis, Andrea (Frontiers in Cellular Neuroscience, 2014)
The plasticity of inhibitory transmission is expected to play a key role in the modulation of neuronal excitability and network function. Over the last two decades, the investigation of the determinants of inhibitory synaptic plasticity has allowed distinguishing presynaptic and postsynaptic mechanisms. While there has been a remarkable progress in the characterization of presynaptically-expressed plasticity of inhibition, the postsynaptic mechanisms of inhibitory long-term synaptic plasticity only begin to be unraveled. At postsynaptic level, the expression of inhibitory synaptic plasticity involves the rearrangement of the postsynaptic molecular components of the GABAergic synapse, including GABAA receptors, scaffold proteins and structural molecules. This implies a dynamic modulation of receptor intracellular trafficking and receptor surface lateral diffusion, along with regulation of the availability and distribution of scaffold proteins. This Review will focus on the mechanisms of the multifaceted molecular reorganization of the inhibitory synapse during postsynaptic plasticity, with special emphasis on the key role of protein dynamics to ensure prompt and reliable activity-dependent adjustments of synaptic strength.